2012
DOI: 10.4269/ajtmh.2012.11-0331
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of Material Durability of Three World Health Organization–Recommended Long-Lasting Insecticidal Nets in Eastern Chad

Abstract: A total of 876 nets (229 Interceptor®, 363 Olyset®, and 284 PermaNet®) were collected 14 months post-distribution of long-lasting insecticidal nets (LLINs) from 811 households of internally displaced and host communities in Dar Sila District in eastern Chad to examine their physical condition. Holes were recorded by using three hole categories (average diameter = 2, 3.5, and 15 cm) and a Proportionate Hole Index (pHI). A total of 69.5% were in poor or very poor condition. There was no significant difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 8 publications
3
74
0
Order By: Relevance
“…Although we were able to quantify the physical durability of the LLINs after 3 years of follow-up, the degree to which the physical damage of an LLIN impacts its ability to protect the individuals sleeping under it from a malaria-infected mosquito is not well understood. 13,23,24,[28][29][30][31][32][33] The pHI, which provides a standardized measure to compare holes among different LLINs by assigning a weight, which is the midpoint diameter to an estimated hole size, 8,[10][11][12][13]23,34 confirmed differences in durability between these two major brands of LLINs. It would seem obvious that very large holes, such as those 25 cm, would easily allow for a mosquito to enter an LLIN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we were able to quantify the physical durability of the LLINs after 3 years of follow-up, the degree to which the physical damage of an LLIN impacts its ability to protect the individuals sleeping under it from a malaria-infected mosquito is not well understood. 13,23,24,[28][29][30][31][32][33] The pHI, which provides a standardized measure to compare holes among different LLINs by assigning a weight, which is the midpoint diameter to an estimated hole size, 8,[10][11][12][13]23,34 confirmed differences in durability between these two major brands of LLINs. It would seem obvious that very large holes, such as those 25 cm, would easily allow for a mosquito to enter an LLIN.…”
Section: Discussionmentioning
confidence: 99%
“…5 Despite the large investment in the procurement and distribution of ITNs and LLINs, which is estimated to have increased from 6 million US dollars (USD) in 2004 to 92 million in 2011, 4 little information exists on the physical durability of LLINs in the field; and few malaria control programs to date have systematically monitored the performance of LLINs in terms of physical durability after mass distributions. [8][9][10][11][12][13][14][15][16] Several studies provide evidence that the levels of insecticide present in LLINs months and years after their distribution remains adequate 10,[17][18][19][20][21][22][23] ; however, this information alone does not entirely address whether LLINs remain effective as a vector control tool over several years of daily use. The physical integrity of the LLIN, specifically the presence of holes, tears, and repairs, needs to be taken into account when determining whether an LLIN is capable of protecting individuals or communities from mosquitoes infected with malaria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] However, field experience shows that LLIN fabric may wear out in as little as 14 months. [18][19][20] In addition, frequent or vigorous net washing and inadequate net handling can greatly reduce the effective life of the insecticide. 21,22 Better net care and maintenance could prolong net life, thus stretching scarce financial resources and minimizing coverage gaps caused by worn nets.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in Tanzania it was observed that LLINs started to show signs of damage after two to three years of regular use [30]. In Chad, a recent study [31] involving field evaluation of two WHO recommended LLINs revealed that 25% LLINs were not fit for use and or repair, while 44.5% required major repairs after one year of use. The damaged and torn LLINs have been shown to increase human-mosquito contact; despite the use of the LLINs, the user received up to five bites per night [3,32].…”
Section: The Physical and Biological Integrity Of Llinsmentioning
confidence: 95%